Long-term patient-reported outcomes following congenital heart surgery in adults - Thibault Schaeffer; Thibault Schaeffer; Pauline Bossers; Doris Kienmoser; Doris Kienmoser; Oktay Tutarel; Paul Philipp Heinisch; Paul Philipp Heinisch; Masamichi Ono; Masamichi Ono; Julie Cleuziou; Julie Cleuziou; et al. (Frontiers in Cardiovascular Medicine)
ObjectiveTo investigate the long-term impact of cardiac surgery on the quality of life in adults with congenital heart disease (ACHDs).MethodsPatients who had undergone cardiac surgery for congenital heart disease (CHD) at the age of 18 years or more were recruited in a single-center, cross-sectional study. The enrolled subjects completed online questionnaires to assess patient-reported outcomes: perceived health status and life satisfaction, psychological functioning, health behaviors, and illness perception. Clinical variables were correlated to the score results, and results were compared to representative samples from international and German national surveys of healthy subjects and ACHDs.ResultsWe enrolled 196 ACHDs (54% women), including 55% with more than one cardiac surgery during their lifetime. The median age at the survey was 43 years, with a median of 13 years since their last cardiac surgery. The majority of patients reported improved subjective wellbeing after cardiac operation and were in functional New York Heart Association class I or II. The severity of underlying CHD, number of previous cardiac operations, and beta-blocker medication had the most substantial negative effects on illness perception. Measured quality of life and health risk behaviors were within the range of values internationally reported for healthy and CHD subjects, respectively.ConclusionsACHD, several years after cardiac surgery, reported a subjective improvement in their wellbeing, a life satisfaction comparable to that of healthy individuals, and low health risk behaviors. Illness perception is strongly correlated with the severity of the underlying CHD.